Shemenova Y. The theme of Judaica in the mural art of Poland (on the example of the murals of the cities of Krakow and lodz) - Shemenova, Yuliia (2020)
The article deals with the appeal to Judaica in the mural art of modern Poland. It reviews interviews and publications of Ukrainian and Polish scholars covering the issues of the genocide of Jews in the lands of Poland and Western Ukraine (Galicia) (Yohanan Petrovsky-Shtern, I. Klimova, E. Schneider, S. Lapenko). It highlights the historical process of the mass extermination of Jews by Nazi Germany during the Second World War (1939–1945) in the territory of Kraków, Auschwitz (Auschwitz), Warsaw and the city of Łódź (Litzmanstadt). The article analyses the artistic-figurative component of the murals of foreign European and local writers in the cities of Kraków and Łódź. Analyzed the scientific research of local researchers, discuss the importance of murals on the streets of the specified cities (K. Porada, I. Jażdżewska). It emphasised the appeal to the theme of Judaica, as one of the main themes in the murals of Kraków. It points out the fact that the choice of the topic covered by local writers was influenced by the status of the Jewish population of Poland, which until 1939 amounted to more than two million people and the events that preceded the mass extermination of the local residents.